1998
DOI: 10.1007/bf02672511
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone formation in the study of postmenopausal osteoporosis

Abstract: A comparative study was performed on the sensitivity of the determination of the available biochemical markers of bone formation--total and bone alkaline phosphatase (TAP and bAP, respectively), osteocalcin (BGP), procollagen I aminoterminal propeptide (PINP) and procollagen I carboxyterminal propeptide (PICP)--in the study of postmenopausal osteoporosis. The comparison between PINP and PICP, due to the recent development of the amino-terminal assay, is of special interest. The study included 26 untreated oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 16 publications
3
5
0
1
Order By: Relevance
“…Pino et al [12] found that osteocalcin is a promising marker of bone turnover useful in the diagnosis and follow-up of high turnover osteoporosis. Similar observations were reported by a number of other studies Verit et al [13], Cabrera et al [14] and Rosenquist et al [15]. Table 1 shows significant decrease in osteocalcin level from baseline to post therapy of 3 months (Alendronate ?…”
Section: Resultssupporting
confidence: 89%
“…Pino et al [12] found that osteocalcin is a promising marker of bone turnover useful in the diagnosis and follow-up of high turnover osteoporosis. Similar observations were reported by a number of other studies Verit et al [13], Cabrera et al [14] and Rosenquist et al [15]. Table 1 shows significant decrease in osteocalcin level from baseline to post therapy of 3 months (Alendronate ?…”
Section: Resultssupporting
confidence: 89%
“…Moreover, in the present study when women were stratified into normal, osteopenic and osteoporotic groups, s-CTX levels were significantly higher in women with spine or femur BMD in the osteoporotic range than in normal or osteopenic women. This finding is in accordance with the observation of Dominguez Cabrera et al 17 and is likely to be linked to an increased bone resorption that occurs in women with osteoporosis and, therefore, is mainly evident in this group of women. But the data around the correlation lines were highly scattered for s-CTX (as well as for BAP and OC), indicating the presence of a considerable interindividual variability.…”
Section: Discussionsupporting
confidence: 93%
“…The finding that PICP and PINP levels were lower in the osteoporotic women than in the early menopausal women is discordant with the results of Dominguez Cabrera et al [24] who found higher levels of these two markers of bone collagen formation in a group of osteoporotic women than in healthy menopausal women. This conflicting point is of interest and deserves further studies as our results suggest a negative balance in collagen turnover in osteoporosis.…”
Section: Discussionsupporting
confidence: 74%